2021
DOI: 10.1093/jhps/hnab022
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported allergies correlate with a worse patient-reported outcome after hip arthroscopy: a matched control study

Abstract: Patient-reported outcome measures (PROMs) in patients with and without at least one self-reported allergy undergoing hip arthroscopy were compared. Data on 1434 cases were retrospectively reviewed, and 267 patients were identified with at least one self-reported allergy and randomly matched to a control group on a 1:2 ratio. Four PROMs [Modified Harris Hip Score (mHHS), Hip Outcome Score-Activities of Daily Living (HOS-ADL), Hip Outcome Score-Sports (HOS-Sport) and 33-item International Hip Outcome Tool (iHOT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…Ultimately, a reasonable conclusion that can be inferred from the above findings is that allergy status should be considered in the context of multiple patient-specific factors that influence arthroscopic outcomes. Based on the results in this study, as well as the results of prior investigations [ 14 , 18 ], it is evident that allergy status is linked to arthroscopic outcome. However, this association is complex in nature and likely reflects the impact of various psychosomatic factors on arthroscopic outcomes.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Ultimately, a reasonable conclusion that can be inferred from the above findings is that allergy status should be considered in the context of multiple patient-specific factors that influence arthroscopic outcomes. Based on the results in this study, as well as the results of prior investigations [ 14 , 18 ], it is evident that allergy status is linked to arthroscopic outcome. However, this association is complex in nature and likely reflects the impact of various psychosomatic factors on arthroscopic outcomes.…”
Section: Discussionsupporting
confidence: 71%
“…Studies have shown that self-reported allergies associate with pre-existing psychiatric conditions and prognosticate risk of developing mood and anxiety disorders in the future [ 16 , 30 ]. This association may explain the results of the present study and similar investigations because psychological factors can influence the postoperative course and compromised mental wellness increases the likelihood of inferior patient-reported outcomes [ 14 , 18 , 31 , 32 ]. Further, preoperative mental health conditions associated with reduced postoperative hip function and poor surgical outcomes [ 15 , 17 , 33 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…conducted a retrospective analysis that found that THA and TKA patients with a higher number of PRAs had a higher risk for prosthetic joint infection (PJI) [ 6 ]. Similar negative associations between PRAs and outcomes have been found for other orthopedic procedures such as spine surgery and hip arthroscopy [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 68%